Convergence and divergence in a long‐term old‐field succession: the importance of spatial scale and species abundance. (4th July 2016) - Li, Shao‐peng; Cadotte, Marc W.; Meiners, Scott J.; Pu, Zhichao; Fukami, Tadashi; Jiang, Lin
Abstract: Whether plant communities in a given region converge towards a particular stable state during succession has long been debated, but rarely tested at a sufficiently long time scale. By analysing a 50‐year continuous study of post‐agricultural secondary succession in New Jersey, USA, we show that the extent of community convergence varies with the spatial scale and species abundance classes. At the larger field scale, abundance‐based dissimilarities among communities decreased over time, indicating convergence of dominant species, whereas incidence‐based dissimilarities showed little temporal tend, indicating no sign of convergence. In contrast, plots within each field diverged in both species composition and abundance. Abundance‐based successional rates decreased over time, whereas rare species and herbaceous plants showed little change in temporal turnover rates. Initial abandonment conditions only influenced community structure early in succession. Overall, our findings provide strong evidence for scale and abundance dependence of stochastic and deterministic processes over old‐field succession.